The linkage of employee satisfaction and loyalty in Hotel Industry in Klang Valley, Malaysia. - Abdullah, Rahman; Abdul Karim, Noraida; Abdul Patah, Mohd Onn Rashidi; Zahari, Harnizam; Sekharan Nair, Gopala Krishnan; Jusoff, Kamaruzaman (Canadian Center of Science and Education, 2009)
Many organizations in the hotel industry face difficulties in retaining employees since they are unable to identify the factors that contribute to both employee satisfaction and loyalty. This study, covers 13 satisfaction variables and 3 loyalty variables. Employment tenure, employee future plan with the company, and recommending employment in the company would be taken as the 3 loyalty indicators in this study. This study sought to identify factors which could lead to increased tenure, in addition, any linkage between employee satisfaction and employee loyalty was investigated. In order to do that, a business model, called the Service Profit Chain was used and applied in hotels in the Klang Valley area in Malaysia. A portion of the model that measures employee satisfaction and employee loyalty was adopted for this study. The findings indicate the existence of a correlation between employee satisfaction and employee loyalty. Four of the thirteen satisfaction variables, namely, relationship with supervisor, recognition and rewards, working conditions, teamwork and cooperation showed the strongest correlation with the three loyalty variables afore mentioned. It is hoped that the findings could be used by managers in the service industries in developing effective employee training programmes by placing emphasis on the four satisfaction variables which correlated strongly with the three loyalty variables. However, since the sample of this study comprises only the front line employees, it is hoped that a future extended study would be carried out which would include the back of the house staff as well. If the findings are similar, then the theories of employee satisfaction and loyalty would apply equally to the entire hotel staff and this would greatly assist hotels in organizing uniform, effective and cost saving training programmes for all the staff to increase the level of employee satisfaction and loyalty for the mutual benefit of the employee and the organization.